Pengaruh Tingkat Pendidikan terhadap Kinerja UMKM Jakarta - Qudsi, Lintang Jawaril; Astuti, Sri; Safitri, Camelia (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Micro, Small and Medium Enterprises (MSMEs) are an economic sector in Indonesia that have an important role in developing the country's economy. Even though MSMEs have a role in the economy, in the course of business there are still obstacles and obstacles faced by MSME actors. These problems include the low level of education and gender issues whose equality is still questionable. This study aims to determine the effect of education level on the performance of MSMEs in Jakarta in terms of gender. The method used in this study is a quantitative method using a random sampling technique with a total sample of 80 respondents from SMEs in Pasar Rebo District. This study took data through a closed questionnaire. The results of this study indicate that the level of education has a significant effect on the performance of MSMEs, whereas if viewed through the gender aspect it does not affect the performance of MSMEs. Keywords: Level of Education, SMEs, and Gender.